(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The formation of a proper body posture is highly affected by body build and proportions. Correct silhouette is usually observed in children with solid constitution. The objective of the study was to evaluate the somatic development of rural children with structural scoliosis as compared to their peers with correct body postures. Investigations into the biological development of rural children and youth were carried out in the years 1998—1999, in primary and secondary schools of the Southern Podlasie region. The study involved 1045 girls and 1025 boys, aged 7—19 years, including 35 subjects with structural scoliosis. Body posture was evaluated based on orthopedic examination, including the Adams’ test. The somatic development of children with structural scoliosis was charac- terized on the basis of the following measurements: body height and mass, arm and shank circumference, elbow and knee width, and Body Mass Index (BMI). The results of measurements were plotted on centile scales, elaborated for rural children of the Southern Podlasie. The results of the study indicate that, in most cases, body sizes of girls and boys with structural scoliosis reached values either meeting or lower than those recommended for rural children. The occurrence of extremely low values of body mass, BMI, musculature and skeleton stoutness measurements as well as extremely high values of body height in the analyzed children with scoliosis seems highly alarming. Keywords: body posture of rural girls and boys, structural scolioses, somatic traits.